EXPLORING LEARNERS’ SPEAKING APPREHENSION IN AN ENGLISH CLASSROOM AT SMPN 5 LANGSA - Shafrida Wati; Zahratul Idami; Anita Anita (Institut Pendidikan Tapanuli Selatan, 2022)
This study explores language apprehension in speaking experienced by learners in a foreign language setting. It further investigates factors contributing to the anxiety and types of anxiety they experienced in practicing English. This research deployed qualitative research with a case study type of research. The subject of this study was 25 students in the ninth grade of SMPN5 Langsa. Observation and interviews were used to collect the data. To analyze the data the researchers used an interactive model of analyses suggested by Miles and Huberman (1994) consisting of data reduction, data display, and conclusion drawing. Findings showed that factors that trigger language apprehension among the learners are low self-efficacy, lack of vocabulary and grammar mastery, de-motivated in learning English, and unsupportive language learning environment. Most of the learners experience state anxiety particularly when they are asked to share their thoughts in English spontaneously and to practice the target language in front of the class.